2014
DOI: 10.1590/0034-7329201400310
|View full text |Cite
|
Sign up to set email alerts
|

A discreta transição da Coreia do Norte: diplomacia de risco e modernização sem reforma

Abstract: A República Popular Democrática da Coreia/RPDC (Coreia do Norte) é um dos Estados menos conhecidos e difíceis de compreender do mundo, e uma das razões disso é a contínua criação política de narrativas ideológicas caricaturais promovidas por atores Ocidentais. Mesmo no meio acadêmico, constitui um tema tabu, o que prejudica a análise de processos em curso, que passam despercebidos. Apesar de considerada um fóssil da Guerra Fria, sempre no limite do colapso, o que se observa é uma população que demonstra vitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The North Korea case was assessed by Cha (2009), Fitzpatrick (2011), and Visentini and Pereira (2014). Similarly, the authors concluded the continuous threat imposed by a very isolated and recalcitrant state, engaged in a political game of concessions and extractions with the U.S. based on its nuclear development.…”
Section: The Obama Administration and The Russian Violationsmentioning
confidence: 99%
“…The North Korea case was assessed by Cha (2009), Fitzpatrick (2011), and Visentini and Pereira (2014). Similarly, the authors concluded the continuous threat imposed by a very isolated and recalcitrant state, engaged in a political game of concessions and extractions with the U.S. based on its nuclear development.…”
Section: The Obama Administration and The Russian Violationsmentioning
confidence: 99%